2018
DOI: 10.15666/aeer/1601_677695
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Tea Endophytic Fungi: Cultivar- And Tissue Preferences

Abstract: Abstract. Endophytic fungi were isolated from four healthy tissues (new leaf, old leaf, bark, and xylem) of three Japanese tea cultivars (Hokumei, Sayamakaori, and Yabukita) at the Saitama Tea Research Institute, Japan in July 2015. A total of 520 isolates was obtained from 600 segments and were classified into 44 fungal taxa; the majority (93.2%) belonged to the phylum Ascomycota. The lowest infection rate was found in the xylem tissue of all cultivars. The total infection rate did not differ significantly am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 27 publications
(38 reference statements)
1
19
0
13
Order By: Relevance
“…The microbial endophyte community in leaves typically differed from those in stems for the two cultivars assessed (‘Royal Gala’ and ‘Braeburn’). This was consistent with previous studies (da Silva et al ; Win et al ; Sadeghi et al ). It is likely due to both ontogenic differences and the mechanisms that recruit micro‐organisms to these tissues in apples (Chi et al ; Herre et al ; Bulgarelli et al ).…”
Section: Discussionsupporting
confidence: 94%
“…The microbial endophyte community in leaves typically differed from those in stems for the two cultivars assessed (‘Royal Gala’ and ‘Braeburn’). This was consistent with previous studies (da Silva et al ; Win et al ; Sadeghi et al ). It is likely due to both ontogenic differences and the mechanisms that recruit micro‐organisms to these tissues in apples (Chi et al ; Herre et al ; Bulgarelli et al ).…”
Section: Discussionsupporting
confidence: 94%
“…It shows that during the maturation of tea leaves, the endophytic bacteria in the leaves are gradually decreasing and the endophytic fungi are gradually increasing, showing the process of succession. Win et al [24] found in the tissue preference study of endophytic fungi in tea plants that Colletotrichum gloeosporioides f. sp. camelliae showed preference in bark and old leaf tissues rather than new leaf and xylem tissues.…”
Section: Effects Of Tissue Types On the Distribution Of Endophytic Fumentioning
confidence: 99%
“…The distribution of endophytic fungi and bacteria showed significant differences among different tea cultivars. Win et al [24] isolated the endophytic fungi of three tea cultivars (Hokumei, Sayamakaori, and Yabukita) in the same tea garden and found that the four common endophytic fungi (Pleosporales sp., Colletotrichum gloeosporioides f. sp. camelliae, Peyronellaea glomerata, and Botryosphaeria dothidea) all showed obvious cultivars preference except Pleosporales sp.…”
Section: Effects Of Tea Cultivars On the Distribution Of Endophytic Fmentioning
confidence: 99%
“…and morpho species were identified from the plant. The genera, Cladosporium was predominantly isolated compared to other fungal species thus illustrating that it is one of the prominent fungal endophytes present in the plant (32). Curvularia sp.…”
Section: Discussionmentioning
confidence: 95%